\(\displaystyle\to\frac{{{2}{x}-{5}}}{{\sqrt{{{x}+{5}}}}}=\)

Multiply by the conjugate PSK(sqrt(x+5))/(sqrt(x+5)) =((2x-5)sqrt(x+5))/(sqrt(x+5)sqrt(x+5))ZSK

\(\displaystyle{\left(\sqrt{{{x}+{5}}}\sqrt{{{x}+{5}}}={x}+{5}\right.}\)

\(\displaystyle={\left({2}{x}-{5}\right)}\frac{{\sqrt{{{x}+{5}}}}}{{{x}+{5}}}\)

Therefore, \(\displaystyle\frac{{{2}{x}-{5}}}{{\sqrt{{{x}+{5}}}}}=\frac{{{\left({2}{x}-{5}\right)}\sqrt{{{x}+{5}}}}}{{{x}+{5}}}\)

Multiply by the conjugate PSK(sqrt(x+5))/(sqrt(x+5)) =((2x-5)sqrt(x+5))/(sqrt(x+5)sqrt(x+5))ZSK

\(\displaystyle{\left(\sqrt{{{x}+{5}}}\sqrt{{{x}+{5}}}={x}+{5}\right.}\)

\(\displaystyle={\left({2}{x}-{5}\right)}\frac{{\sqrt{{{x}+{5}}}}}{{{x}+{5}}}\)

Therefore, \(\displaystyle\frac{{{2}{x}-{5}}}{{\sqrt{{{x}+{5}}}}}=\frac{{{\left({2}{x}-{5}\right)}\sqrt{{{x}+{5}}}}}{{{x}+{5}}}\)